Is Israeli Millennials’ Web Comedy Less Politically Engaged? How Social Media Might Hamper Satire - Rosen, Ido (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
This paper claims that Israeli web content creators are less politically engaged and overtly critical in comparison to local filmmakers who have been creating for cinema and television. Their comedy leans towards lighthearted nonsense and avoids taking a stand on controversial topics. It is argued that this can be explained by both universal and uniquely local reasons. In general, web creators are not judged by the same standards of artistic quality that is attributed to films and TV shows. Therefore, they choose different topics and aesthetics, which might appear less “substantial” or “artistic” by traditional perceptions. Also, Millennials are often considered by critics to be less rebellious and more self-centered. In addition, Israeli society has become more right-wing, nationalist, and religious. Contemporary culture therefore favors crowd-pleasing optimism over critique or complaints that ‘spoil the party’. Furthermore, artists’ self-censorship is affected by a growing lack of tolerance, which is sometimes expressed through social media outrage, and might cause severe damage to their careers. Based on these explanations, this paper then analyzes three independent web comedies which touch upon the debatable topic of Jewish settlements in the occupied territories, and the national-religious community, yet do it with varying degrees of criticism.